HUBUNGAN TAYANGAN IMAJINATIF DENGAN POLA KOMUNIKASI PADA ANAK USIA PRASEKOLAH DITAMAN KANAK KANAK RIYANTI BTN TAMARUNANG KABUPATEN GOWA - Audah Mannan; Rustiakhil Hukmi (Fakultas Dakwah dan Komunikasi, 2016)
This research is aimed to find outp the frequency of watching on imaginative cartoon channel toward communication pattern at the pre-school children (3-6-year-old) in TK Rianti BTN Tamarunang, Kabupaten Gowa. To identify the differences between the communication pattern of the boys and the daughters in TK Rianti BTN Tamarunang, Kabupaten Gowa. The type of this research is correlational aassociative research by quantitative approach. The data are collected from pupils in Taman Kanak-Kanak Riyanti BTN Tamarunang, Kabupaten Gowa. The collecting data is through observation and questionnaire. The sampling technique is through total sampling. The data analysis is executed by SPSS verse 23.0. The result of this research indicates that based on chis-square test can be known df 4 with the point of chi-square 9.49 table. It is due to chis-quare about 2.739 < chis quare table about 9.49, then HO is rejected, and Hi is accepted which means that there is a significant relation and relation of imaginative cartoon channe who like giving a help in Taman Kanak-Kanak Riyanti BTN Tamarunang, Kabupaten Gowa. According to the research points out that the attitude of the boys who are on the high level is about ten boys, though the numbers of daughters are bigger than boys. However, it clarifies that the communicaton pattern of the boys are on the higher than the daughters which strongly indicates there is different attitude between the boys and the daugthers.